Improving the socio-ecological fit in water governance by enhancing coordination of ecosystem services used. Issue 139 (January 2023) - Pahl-Wostl, Claudia; Lukat, Evelyn; Stein, Ulf; Tröltzsch, Jenny; Yousefi, Ali
Abstract: Water governance systems have evolved around the exploitation of provisioning ecosystem services. The overexploitation of provisioning and the degradation of regulating services have led to a decline in the capacity of ecosystems to provide any services at all. Decisions affecting water-related ecosystem services are often not made in the water sector. Governance that does not take into account ecological interdependencies lead to unsustainable use of resources. In such situations, one can speak of a misfit between interdependencies of ecosystem services and coordination processes that would allow addressing them. The article introduces an approach to identify such misfits and potential solutions to overcome them and applies the approach to case studies in Germany, South Africa and Iran. The context-sensitive analyses highlight factors that contribute to or even determine prevailing practices in water management. The fit with the pattern of ecosystem service uses was found to be higher for governance processes in practice (formal and informal) than for formal coordination instruments on paper. Actors may not lack opportunities to exchange but these are not translated into tangible coordination outcomes. To reduce trade-offs between the uses of ecosystem service, improved synergies are needed between formal and informal institutional settings. Instruments need to be tailored to local circumstances. Scope and effectiveness of local action may be limited by higher governance levels. The analyses have demonstrated that the path from improving social-ecological fit to achieving sustainability is long. Addressing institutional deficits requires transformational change rather than short-term measures for addressing isolated problems or crisis situations. Highlights: New approach to identify misfits between ecosystem services uses and coordination and potential solutions to overcome them. Results from case studies in Germany, South Africa and Iran. Synergies needed between formal and informal institutional at local level to reduce trade-offs between ecosystem services.